Establishment of a Prediction Model for the Residual Stress on the Surface Layer of Face Gears During Hot Rolling - Jin Yuanyuan; Xu Hongyu; Li Li; Zhang Fengshou; Wang Xiaoqiang; Zhang Guang (Jixie chuandong)
In order to predict the peak value of residual compressive stress and the depth of residual compressive stress layer on the surface of hot rolling gear profiles, the machining process of face gears during hot rolling is simulated by DEFORM-3D finite element simulation software, and the peak value of residual compressive stress and the depth of residual compressive stress layer on the surface of gear profile under different combinations of process parameters are obtained. Taking the simulation results as data samples, the response surface method is used to establish the prediction model of residual compressive stress and compressive stress layer depth on the surface of hot rolling gear profiles, and the optimal process combination is obtained by taking the maximum peak value of residual compressive stress and the minimum depth of residual compressive stress layer as the optimization objective. Taking the optimal process combination as the actual processing parameters, the measured value of residual stress on the surface of tooth profile is compared with the predicted value. It is found that the measured value is less than the predicted value, and the maximum error is no more than 17%. The results show that the prediction model can measure and control the surface residual stress of hot rolling gears.